2023
DOI: 10.3390/pr11020369
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Real-Time Fault Diagnosis Methods for Industrial Smart Manufacturing

Abstract: In the era of Industry 4.0, highly complex production equipment is becoming increasingly integrated and intelligent, posing new challenges for data-driven process monitoring and fault diagnosis. Technologies such as IIoT, CPS, and AI are seeing increasing use in modern industrial smart manufacturing. Cloud computing and big data storage greatly facilitate the processing and management of industrial information flow, which helps the development of real-time fault diagnosis (RTFD) technology. This paper provides… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(14 citation statements)
references
References 115 publications
0
14
0
Order By: Relevance
“…Ultimately, the trained network is employed for diagnosing faults in new monitoring data. Some deep hierarchical networks can even directly process source data as input for real-time monitoring [107].…”
Section: Quantitative Methodsmentioning
confidence: 99%
“…Ultimately, the trained network is employed for diagnosing faults in new monitoring data. Some deep hierarchical networks can even directly process source data as input for real-time monitoring [107].…”
Section: Quantitative Methodsmentioning
confidence: 99%
“…The algorithm demonstrated that, when applied alongside diagnosis models such as Support Vector Machines (SVM) and k-Nearest Neighbour (kNN), As previously mentioned, the complexity of the CNC machines and the noisy nature of the industrial environment makes the application of a holistic CBM system difficult, thus separating into its critical subsystems is crucial. In the literature, CBM and its application has a wide variety of research papers and reviews available in this field alone, some recently published review papers are referenced for the reader [5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7] Among existing data-driven fault detection methods, multivariate analysis (MVA) techniques including principal component analysis (PCA) and partial least squares (PLS) are recognized as powerful and efficient tools for addressing the fault detection problems in the process industry. [8][9][10][11][12] Nevertheless, in PCA-based process monitoring methods, the relationship between the input and output variables has not been taken into consideration. The valuable information within the input and output relationship has not been exploited enough.…”
Section: Introductionmentioning
confidence: 99%